MERDEKA BELAJAR IN ACCOUNTING EDUCATION STUDENT PERSPECTIVE - Elana Era Yusdita; Elly Astuti; Tika Panjawiyati; Lina Nuryani (Universitas PGRI Madiun, 2022)
ABSTRACTMBKM is a policy that frees students to synchronize learning activities with their needs in a rapidly changing future. This study was conducted to determine whether the MBKM program implemented was on the perception of independent learning for the students involved. Researchers used phenomenology with data collection techniques through interviews, observations, and documentaries. The results showed that in entrepreneurial activities, students felt free to learn because they had the experience of starting a business from scratch. Teaching assistant participants feel free because they can practice their courage to speak in public and experience developing modules. Research participants benefit from research and development knowledge and have the opportunity to create LKPD. Industrial apprentices are not independent because they are not fully involved in partner operational activities.ABSTRAKMBKM merupakan kebijakan yang membebaskan mahasiswa untuk melakukan sinkronisasi kegiatan pembelajaran dengan kebutuhannya dalam menyongsong masa depan yang berubah dengan cepat. Penelitian ini dilakukan untuk mengetahui apakah program MBKM yang diimplementasikan sesuai dengan persepsi merdeka belajar bagi mahasiswa yang terlibat. Peneliti menggunakan fenomenologi dengan teknik pengumpulan data melalui wawancara, observasi, serta dokumentasi. Hasil penelitian menunjukkan bahwa pada aktivitas kewirausahaan mahasiswa merasa telah merdeka belajar karena mendapat pengalaman merintis usaha dari nol. Peserta asistensi mengajar merasa merdeka karena dapat melatih keberanian berbicara di depan umum sekaligus berpengalaman membuat modul. Peserta penelitian mendapat manfaat pengetahuan penelitian pengembangan dan berkesempatan membuat LKPD. Peserta magang industri belum merasa merdeka karena tidak terlibat secara penuh dalam kegiatan operasional mitra.